Powder-Based 3D Printed Porous Structure and Its Application as Bone Scaffold - Zhao, Yingchun; Hou, Yue; Li, Zhaoyu; Wang, Ziyu; Yan, Xinxin (Frontiers in Materials, 2020)
Customized porous structures are widely used in bone tissue engineering as bone substitutes. In natural bone, the bone tissue relies on the blood vessels in the vesicular structure for nutrition supply. When a defect appears, the biomimetic porous scaffold becomes a good candidate for the formation of new blood vessels and helps bone tissue ingrowth. To construct an osteoconductive bone scaffold that is suitable for the defect region, the powder-based three-dimensional printing technology holds great promise, since it can deal with biocompatible, and biodegradable materials. In this mini-review, we introduce several types of powder-based manufacturing technologies and their corresponding printable materials for the construction of porous structures. In addition, some research cases are highlighted to illustrate the recent development of some research directions related to powder-based 3D printed bone scaffolds.